Feedback regulation in multistage cell lineages - Wing-Cheong Lo; Ching-Shan Chou; Kimberly K. Gokoffski; Frederic Y.-M. Wan; Arthur D. Lander; Anne L. Calof; Qing Nie (Mathematical Biosciences and Engineering)
Studies of developing and self-renewing tissues have shown thatdifferentiated cell types are typically specified through the actions ofmultistage cell lineages. Such lineages commonly include a stem celland multiple progenitor (transit amplifying; TA) cell stages, which ultimatelygive rise to terminally differentiated (TD) cells. In several cases, self-renewaland differentiation of stem and progenitor cells within such lineages have beenshown to be under feedback regulation. Together, the existence of multiple cellstages within a lineage and complex feedback regulation are thought to conferupon a tissue the ability to autoregulate development and regeneration,in terms of both cell number (total tissue volume) and cell identity(the proportions of different cell types, especially TD cells, within the tissue).In this paper, we model neurogenesis in the olfactory epithelium (OE) of the mouse,a system in which the lineage stages and mediators of feedback regulation that governthe generation of terminally differentiated olfactory receptor neurons (ORNs) have beenthe subject of much experimental work. Here we report on the existence and uniquenessof steady states in this system, as well as local and global stability of these steady states.In particular, we identify parameter conditions for the stability of the system when negativefeedback loops are represented either as Hill functions, or in more general terms.Our results suggest that two factors -- autoregulation of the proliferation oftransit amplifying (TA) progenitor cells, and a low death rate of TD cells -- enhance the stability of this system.